Clinical evaluation of the AutoMicrobic system Yeast Biochemical Card for rapid identification of medically important yeasts. - Oblack, D L (1981)
The autoMicrobic system Yeast Biochemical Card (Vitek Systems, Inc., subsidiary of McDonnell Douglas, Hazelwood, Mo.), a fully automated and computer-assisted method for identifying seven yeast genera based on 26 biochemical reactions, was compared with the API 20C (Analytab Products, Plainview, N.Y) yeast identification system, using 253 clinical yeast isolates. There was an 84% correlation between the Yeast Biochemical Card and API 20C systems based on biochemical tests alone and a 96% correlation when morphology was combined with the biochemical profile. Of 22 species examined, 14 were definitively identified within 24 h, using only the biochemical tests; the remaining 8 species were presumptively identified, using biochemical tests within 24 h, with definitive identification being completed in 48 to 72 h when morphological characteristics were ascertained. The Yeast Biochemical Card system was both a facile and, with concomitant morphology, an accurate system for performing yeast identification.